Effect of ethylene on postharvest strawberry fruit tissue biochemistry - Elmi, Fardusa; Pradas, I.; Tosetti, Roberta; Cools, K.; Terry, Leon A. (International Society for Horticultural Science (ISHS), 2017)
The effect of continuous ethylene supplementation (50 µL L-1) on cold-stored strawberry fruit physiology and biochemistry, including phytohormone (abscisic acid) metabolism was investigated. In comparison with control fruit which exhibited high sucrose and malic acid contents during storage, ethylene-treated fruits showed increased respiration, sucrose hydrolysis and concomitant reducing sugars accumulation. Ethylene supplementation did not have any effect on phenolic profile. ABA biosynthesis, in both flesh and achenes, was promoted by ethylene. The results herein suggest that controlling ethylene after harvest could suppress senescence and extend shelf-life.
Keywords: abscisic acid; continuous ethylene supplementation; senescence; shelf-life; sugars hydrolysis